2000
DOI: 10.1002/(sici)1097-461x(2000)77:1<376::aid-qua37>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Shannon entropy of chemical changes:SN2 displacement reactions

Abstract: The Shannon entropies along the intrinsic reaction coordinates (IRC) of two S N 2 reactions were calculated at the RHF/6-31++G * * level. The resulting entropic profiles were compared with the corresponding energy profiles. The Shannon entropy profiles in position and momentum space, as well as their sum, show interesting features about the bond forming and breaking process that are not apparent from the conventional reaction energy profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The phase aspect of molecular states was shown to be vital for distinguishing the hypothetical bonded (entangled) and nonbonded (disentangled) states of molecular subsystems in reactive systems, for the same set of the fragment electron densities. The resultant-information analysis of reactivity phenomena complements earlier classical IT approaches to chemical reactions [110][111][112] as well as the catastrophe-theory or quantum-topology descriptions [113][114][115]. One also recalls a close connection between the ELF criterion of electron localization and the nonadditive component of the molecular Fisher information [46,56].…”
Section: Discussionmentioning
confidence: 70%
“…The phase aspect of molecular states was shown to be vital for distinguishing the hypothetical bonded (entangled) and nonbonded (disentangled) states of molecular subsystems in reactive systems, for the same set of the fragment electron densities. The resultant-information analysis of reactivity phenomena complements earlier classical IT approaches to chemical reactions [110][111][112] as well as the catastrophe-theory or quantum-topology descriptions [113][114][115]. One also recalls a close connection between the ELF criterion of electron localization and the nonadditive component of the molecular Fisher information [46,56].…”
Section: Discussionmentioning
confidence: 70%
“…Using Equation ( 26), the authors of [77] found that the minimum of ΔSKL corresponds to the activation barrier and TS of the studied chemical reactions (proton transfer and SN2 reaction) (Figure 8). As for the application of the continual information entropy approach to chemical reactions, we pay attention to two works [73,76]. The work of Ho et al [76] used S ρ and some related quantities to check their changes upon simplest S N 2 displacement reactions.…”
Section: Moleculementioning
confidence: 99%
“…As for the application of the continual information entropy approach to chemical reactions, we pay attention to two works [73,76]. The work of Ho et al [76] used S ρ and some related quantities to check their changes upon simplest S N 2 displacement reactions. Although function S ρ = f (ξ) (ξ is the reaction coordinate) still shows the redistribution of electron density upon the reactions, the authors have not found any specific behavior of the function in the stationary points lying on the reaction path (minima of reactants/products and saddle point of a transition state).…”
Section: Moleculementioning
confidence: 99%
“…Moreover, Balakrishnan et al showed that information-theoretic entropies increase to a maximum in a dynamical study when studying the time evolution of a bimolecular exchange reaction. Within the context of Information Theory, Shannon entropy studies revealed geometrical aspects of the density that are not present in the energy profile of elementary S N 2 reactions . Moreover, Knoerr et al found correlations between charge density aspects of the S N 2 reaction and the energy-related measures of Shaik et al Later, Tachibana identified the chemical bond-forming of model reactions through the kinetic energy density to identify several stages of the reactions along the IRC.…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of Information Theory, Shannon entropy studies revealed geometrical aspects of the density that are not present in the energy profile of elementary S N 2 reactions. 23 Moreover, Knoerr et al 24 found correlations between charge density aspects of the S N 2 reaction and the energy-related measures of Shaik et al 25 Later, Tachibana 26 identified the chemical bond-forming of model reactions through the kinetic energy density to identify several stages of the reactions along the IRC. Also, long-range dipole moments have been useful for ion–molecule reactions to control their reaction path with laser fields.…”
Section: Introductionmentioning
confidence: 99%